2022
DOI: 10.3390/en15165913
|View full text |Cite
|
Sign up to set email alerts
|

Study on Critical Drawdown Pressure of Sanding for Wellbore of Underground Gas Storage in a Depleted Gas Reservoir

Abstract: Accurately predicting the critical differential pressure (CDP) of sand production contributes to improving the peak-shaving capacity and ensuring safe operation of underground gas storage (UGS). The CDP of sanding production in the target wells of the UGS was predicted coupling laboratory tests, inversed analysis with well logging data and numerical simulations. The in-situ mechanical properties of rock were estimated by coupling the laboratory test results and well-logging data. The in-situ stress field of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This method uses the true triaxial stress chamber (TTSC) to simulate the single-hole sanding behavior under true triaxial stress and fluid flow conditions and is verified by the finite element software ABAQUS (Younessi et al, 2013). Studies suggest that there is a critical drawdown pressure difference to induce sand production in the sand producing area around the borehole (Song et al, 2022). The failure prediction under true triaxial stress state is more accurate than Drucker-Prager (Al-Ajmi and Zimmerman, 2005;Al-Ajmi and Zimmerman, 2006) and has a stronger correlation with the experimental results.…”
Section: Critical Drawdown Pressure Difference Evaluationmentioning
confidence: 99%
“…This method uses the true triaxial stress chamber (TTSC) to simulate the single-hole sanding behavior under true triaxial stress and fluid flow conditions and is verified by the finite element software ABAQUS (Younessi et al, 2013). Studies suggest that there is a critical drawdown pressure difference to induce sand production in the sand producing area around the borehole (Song et al, 2022). The failure prediction under true triaxial stress state is more accurate than Drucker-Prager (Al-Ajmi and Zimmerman, 2005;Al-Ajmi and Zimmerman, 2006) and has a stronger correlation with the experimental results.…”
Section: Critical Drawdown Pressure Difference Evaluationmentioning
confidence: 99%
“…There is a correlation between porosity, permeability with effective stress. The pore volume and permeability of rocks decrease with the increase of the cycle of pressure reciprocating changes (Ranjith et al, 2013;Song et al, 2022). The natural gas in the UGS is stored and migrated in the fractures and pores of the reservoir, with the injection production of the UGS, the internal characteristics of the reservoir are also changing (Dake, 1983;Gobran et al, 1987;Economides and Nolte, 1989;Cosentino, 2001;Lucia et al, 2003;Jaeger et al, 2009;Lake, 2012;Ahmed, 2018) (Figure 4).…”
Section: Injection Production Capacity Characterizationmentioning
confidence: 99%
“…In the multi‐cycling injection–production process, the sanding production with the high‐speed natural gas in the depleted oil and gas reservoir will erose the strings, valves, and other equipment. Many UGS in the depleted oil and gas reservoir have faced the engineering challenges of sanding production, such as Wen 96, Wen 23, Hutubi in China, 8 Redfield, Vincent, 9 Hillsboro 10 in America, Hajdúszoboszló, 11 Haidach 12 in Europe. Thus, a deep understanding of the sanding production in the depleted oil and gas reservoir contributes to maintaining the injection and production capacity of gas storage and the long‐term safety of the UGS.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al accurately predicted CDP based on inversion results of numerical simulation of the geo‐stress in the target reservoir, combined with experiments and logging data. It showed that the depletion of reservoir pressure and the increase of water saturation will also lead to the decrease of CDP 8 . Thus, to guarantee the safe production, accurate prediction of the critical drawdown pressure (CDP) of UGS is necessary for predicting the sand production problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation